Tuning the photocatalytic water-splitting capability of two-dimensional α-In2Se3 by strain-driven band gap engineering. Issue 6 (29th January 2020) - Procopio, Erik F.; Pedrosa, Renan N.; L. de Souza, Fábio A.; Paz, Wendel S.; Scopel, Wanderlã L.
Abstract : In this work, we have investigated the effects of in-plane mechanical strains on the electronic properties of single-layer α-In2 Se3 by means of density functional theory (DFT) calculations. Abstract : In this work, we have investigated the effects of in-plane mechanical strains on the electronic properties of single-layer α-In2 Se3 by means of density functional theory (DFT) calculations. Our findings reveal that this system exhibits a semiconductor character with an indirect band gap in the ground state, with a compressive biaxial strain leading to an indirect to direct band gap transition. Remarkably, along with the band gap transition, the system displays promising capability to produce hydrogen gas from a visible light photocatalytic water splitting process.